Monitoring technology of hydroturbines in pumped storage power stations: a mini review - Yang, Zhangbin; Yuan, Hongping; Cai, Xi; Lian, Xueguang; Mao, Jiang; Shi, Xiangjian (Frontiers in Energy Research, 2024)
Regarding the monitoring and control technology of pumped storage power stations, the monitoring methods for the operating parameters of the turbines in pumped storage power stations were first analyzed, including the monitoring locations and methods for pressure and vibration, as well as the analysis of the reasons for special operating conditions; Secondly, the operation monitoring and fault diagnosis system of pumped storage power stations was summarized and introduced, including the commonly used monitoring systems, fault diagnosis principles, and application situations. Finally, the development trend of turbine monitoring technology and fault diagnosis was discussed.